Dyeing Cotton, Wool, and Silk with Allium Cepa (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Through the use of a dip-dry-iron-cure procedure, cotton fabric was treated with maleic anhydride, Allium cepa, and Terminalia arjuna all at once, with sodium citrate serving as an catalyst for esterification and free radical polymerization using potassium peroxodisulfate. Dyeing silk and cotton fabric with itaconic acid and maleic anhydride, or both, under the combined Catalysts for esterification and free radical polymerization caused chain polymer cross-linking to a certain extent, according to infrared analysis of the dyed fabrics. The purpose of this thesis is to increase the performance and versatility of dyed substrates by improving the balance of their qualities via the use of natural dyes applied to silk and cotton textiles.